2004
DOI: 10.1037/0278-7393.30.3.675
|View full text |Cite
|
Sign up to set email alerts
|

Horizontal Information Flow in Spoken Sentence Production.

Abstract: In 4 experiments the authors used a variant of the picture-word interference paradigm to investigate whether there is a temporal overlap in the activation of words during sentence production and whether there is a flow of semantic and phonological information between them. Experiments 1 and 2 demonstrate that 2 semantically related nouns produce interference effects either when they are in the same or different phrases of a sentence. Experiments 3 and 4 demonstrate that 2 phonologically related nouns produce f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
107
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(124 citation statements)
references
References 52 publications
15
107
2
Order By: Relevance
“…It has been shown that when semantically related nouns are planned and uttered close to each other, production difficulty increases (Smith & Wheeldon, 2004), possibly because speakers need to inhibit one of the nouns when producing the other noun but later have to retrieve it. MacDonald (2013) argues that this similarity-based interference may influence the choice of utterance form.…”
Section: Why Verb-medial Responses?mentioning
confidence: 99%
“…It has been shown that when semantically related nouns are planned and uttered close to each other, production difficulty increases (Smith & Wheeldon, 2004), possibly because speakers need to inhibit one of the nouns when producing the other noun but later have to retrieve it. MacDonald (2013) argues that this similarity-based interference may influence the choice of utterance form.…”
Section: Why Verb-medial Responses?mentioning
confidence: 99%
“…The interference effect was stronger in the near than in the middle condition. One account of these semantic interference effects is that the selection of the lemma for the first noun is slowed down by the co-activation of the related second lemma (e.g., Freedman, Martin, & Biegler, 2004;Smith & Wheeldon, 2004). Thus, co-activation of a second lemma was more likely in the near and middle conditions, where the second object could be identified while the first one was fixated upon.…”
Section: Introductionmentioning
confidence: 99%
“…Although this seems a cognitively costly task, it is unlikely that speakers plan word by word, as this would result in influent speech (Jaeger, Furth, & Hilliard, 2012;Smith & Wheeldon, 2004). It is also unlikely that the surface form of an entire message has been planned before articulation of a sentence, as this would result in a larger span and proportion of phonological errors than what is usually observed in healthy speakers.…”
mentioning
confidence: 99%